Analysis of Digital Communication Patterns in the Institutional Business Division of PT Bank Rakyat Indonesia (Persero) Tbk - Putri, Zahra Heidi; Febriantina, Susan; Maulida, Ervina (Dinasti Publisher, 2025)
This study aims to analyze the digital communication patterns in the Institutional Business Division of PT Bank Rakyat Indonesia (Persero) Tbk. In today’s digital era, effective communication is crucial to support smooth operations and relationships between internal and external parties. This research uses a descriptive qualitative approach, with data collected through direct observation and in-depth interviews with employees in the division. The results show that the division utilizes various digital communication platforms such as WhatsApp, email, Zoom, and Microsoft Teams, for both formal and informal communication. However, several challenges were identified, including miscommunication, information overload, and technical issues such as unstable signal quality. Miscommunication often occurs due to the limited non-verbal expression in text-based communication. The study also found that digital communication facilitates coordination among teams and speeds up decision-making. However, challenges such as difficulty in understanding the context of messages and information overload need to be addressed to enhance communication effectiveness. Based on these findings, it is recommended that the company enhance digital literacy and optimize communication platforms to support digital communication effectiveness within the organization.